Potensi Daya Tarik Gastronomi Wisata Kuliner sebagai Faktor Kunci dalam Mengembangkan Pariwisata Kuliner Pempek 26 Ilir Palembang - Sauky, Muhammad; Misnawati, Desy (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Gastronomy tourism is an important aspect of the tourism industry which is able to attract the attention of visitors from various corners of the world. One of the special foods that stands out in Palembang is pempek, especially Pempek 26 Ilir. This research aims to reveal the potential gastronomic of Pempek 26 Ilir Palembang as the main attraction for tourists. The theories used are Symbolic Communication Theory and Tourist Experience Theory. The research method used involved surveys, interviews, and direct observation of visitors and owners of pempek culinary businesses in the Pempek 26 Ilir area. The research results show that Pempek 26 Ilir has a strong appeal in various gastronomic aspects. The unique taste and texture of pempek, as well as the variety of cuko (gravy) and accompaniments, make visitors come back again to enjoy this dish. Apart from that, the local culinary potential and the pempek raw materials quality are also added value to the culinary experience. The comfortable atmosphere of the stall, the closeness between the owner and visitors, as well as various special promotional programs also enrich the gastronomic experience of tourists. The potential gastronomic attraction of Pempek 26 Ilir Palembang can be a basis for related parties to develop and promote culinary tourism in Palembang. Thus, it can increase tourist visits and contribute to the local economy.